Preparation and anti-leakage properties of hydroxyethyl cellulose-g-poly (butyl acrylate-co-vinyl acetate) emulsion. (1st March 2021) - Liu, Xiaomei; Zeng, Wei; Zhao, Junji; Qiu, Xueyan; Xiong, Hongran; Liang, Yan; Ye, Xie; Lei, Ziqiang; Chen, Denglong
Highlights: A new low-cost and environmentally friendly acrylic emulsion was synthesized. The emulsion had higher thermal stability than hydroxyethyl cellulose. The emulsion interacted with attapulgite to form a dense consolidation layer. The emulsion exhibited excellent anti-leakage performance and water retention. Abstract: A hydroxyethyl cellulose-g-poly (butyl acrylate-co-vinyl acetate)(HEC-g-P (BA-co-VAc)) emulsion was synthesized by free radical emulsion polymerization method from hydroxyethyl cellulose (HEC), butyl acrylate (BA) and vinyl acetate (VAc) in the presence of emulsifier sodium dodecyl benzene sulfonate (SDBS). The structure, thermal stability and morphology of the emulsion were characterized by Fourier-transform infrared (FTIR), thermogravimetric analysis (TGA), transmission electron microscope (TEM) and other analytical techniques. The results proved that BA and VAc monomers had grafted with HEC. Its thermal stability was also significantly improved compared to HEC. Moreover, the prepared emulsion was evaluated to study the performance of preventing water leakage in soil. Compared with the published anti-leakage materials prepared by directly doping hydroxyethyl cellulose, the emulsion interacted with attapulgite to form a dense consolidation layer, which had better anti-leakage performance and water retention. Therefore, the material was more favorable for popularization and application in arid and semi-arid areas.